Prototipe Kepemimpinan Kiai di Pesantren Tradisional - Nurhadi Kastamin; Abas Mansur Tamam; Nur Afif (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2021)
The position of the kiai as a leader and central figure in values and governance in the life of traditional Islamic boarding schools, resulting in the progress and decline or decline and the development of institutions or institutions of Islamic boarding schools depends a lot on the personality and strength of the kiai. Generally, if a kiai dies, the leadership of the Islamic boarding school will be continued by the descendants or family of the kiai concerned. The purpose of this study is to examine and describe how the model or leadership style of a kiai in a traditional Islamic boarding school. This research is a type of library research, namely the data or materials needed in completing the research obtained from the library in the form of books, encyclopedias, dictionaries, journals, documents, magazines and so on (Hadi, 1990).